Correlation between clinical presentation, peroperative finding and histopathological report in acute appendicitis. - Khan, SA; Gafur, MA; Islam, A; Rahman, MS (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2011 Oct;20(4):570-7 The abstract of this article is available on the PubMed website